Modelling the Species Distribution of Flat-Headed Cats (Prionailurus planiceps), an Endangered South-East Asian Small Felid - Wilting, Andreas; Cord, Anna; Hearn, Andrew J.; Hesse, Deike; Mohamed, Azlan; Traeholdt, Carl; Cheyne, Susan M.; Sunarto, Sunarto; Mohd-Azlan, J.; Ross, Joanna; Shapiro, Aure´ lie C.; Sebastian, Anthony; et al. (Plos One Publishing, 2010)
Background: The flat-headed cat (Prionailurus planiceps) is one of the world’s least known, highly threatened felids with a distribution restricted to tropical lowland rainforests in Peninsular Thailand/Malaysia, Borneo and Sumatra. Throughout its geographic range large-scale anthropogenic transformation processes, including the pollution of fresh-water river systems and landscape fragmentation, raise concerns regarding its conservation status. Despite an increasing number of cameratrapping field surveys for carnivores in South-East Asia during the past two decades, few of these studies recorded the flatheaded cat.